2021
DOI: 10.1007/s10664-020-09933-5
|View full text |Cite
|
Sign up to set email alerts
|

An automated framework for the extraction of semantic legal metadata from legal texts

Abstract: Semantic legal metadata provides information that helps with understanding and interpreting legal provisions. Such metadata is therefore important for the systematic analysis of legal requirements. However, manually enhancing a large legal corpus with semantic metadata is prohibitively expensive. Our work is motivated by two observations: (1) the existing requirements engineering (RE) literature does not provide a harmonized view on the semantic metadata types that are useful for legal requirements analysis; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…The texture feature of an image describes the arrangement of the components of each object in the image, and it is a periodically changing visual element. There are three commonly used texture feature extraction methods, which are statistics-based texture feature extraction method, signal processing-based texture feature extraction method, and structure-based feature extraction method [17][18][19][20]. The research object of the texture feature extraction method based on statistics is the gray value of the current pixel, and the extracted texture feature is the first or higher derivative statistical information of gray.…”
Section: Feature Extractionmentioning
confidence: 99%
“…The texture feature of an image describes the arrangement of the components of each object in the image, and it is a periodically changing visual element. There are three commonly used texture feature extraction methods, which are statistics-based texture feature extraction method, signal processing-based texture feature extraction method, and structure-based feature extraction method [17][18][19][20]. The research object of the texture feature extraction method based on statistics is the gray value of the current pixel, and the extracted texture feature is the first or higher derivative statistical information of gray.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Existing regulatory RE methods for addressing regulatory norms and requirements at a semantic level do seldom consider the peculiar nature of legal norms. Semantic analysis methods (e.g., [5,31]) assume that it is possible to derive requirements from the regulations' immediate analysis (e.g., using an upper ontology [5] or semantic metadata [31]). However, legal scholarship provides a different perspective on the nature of regulatory norms and their meaning, as discussed next.…”
Section: Limitations In Semantic Analysismentioning
confidence: 99%
“…Previous research in linguistics found that the language of law is characterized by specific rules of entailment, dependent on its syntactic structures [20]. Previous regulatory RE research has paid attention to concepts that can be used for the semantic analysis of regulations (e.g., as a part of an upper-ontology [5] or as a system of semantic metadata concepts [31]). It is widely accepted that regulatory norms are expressed in the form of rights and obligations [31].…”
Section: Non-structured Approach Regulation Syntaxmentioning
confidence: 99%
See 2 more Smart Citations